TINGKAT LITERASI EKONOMI MAHASISWA ADMINISTRASI KESEHATAN DALAM MEMAHAMI KONSEP PELAYANAN KESEHATAN - Arisetiawan, Jati Wahyu; Azahra, Alifta Lutfia; Sukma, Cahaya Bidara (LPPM UM Metro, 2025)
This study aims to describe the level of economic literacy of students of the Health Administration Study Program, Ivet University, Semarang, especially in understanding economic concepts relevant to health services. This study uses a descriptive quantitative approach with a questionnaire instrument as a data collection medium that covers eight indicators of economic literacy, and involves 23 third semester students. Data were analyzed using percentage and score categorization techniques. The results showed that the majority of students had a fairly good level of economic literacy in almost all indicators, such as understanding of demand and supply, elasticity, consumer behavior, market concepts, service management, and the influence of government policies on the health system. However, there were a small number of students who still showed a sufficient level of understanding. These findings indicate that the integration of Health Economics courses can make a positive contribution to improving students' economic literacy. This study recommends the development of a more applicable curriculum and the implementation of further studies with a wider scope and a mixed-method approach to explore students' understanding in more depth.